2020
DOI: 10.3390/pathogens9030199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inactivated Mycobacterium bovis Vaccination on Molokai-Origin Wild Pigs Experimentally Infected with Virulent M. bovis

Abstract: The wild pig population on Molokai, Hawaii, USA is a possible reservoir for bovine tuberculosis, caused by Mycobacterium bovis, and has been implicated in decades past as the source of disease for the island's domestic cattle. Heat-inactivated vaccines have been effective for reducing disease prevalence in wild boar in Spain and could prove useful for managing M. bovis in Molokai wild pigs. We designed an experiment to test this vaccine in wild pigs of Molokai genetics. Fifteen 3-4-month-old pigs were orally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Nowadays, there is a certain degree of background regarding the inactivated vaccine candidate based on M. bovis (HIMB), that have been reported to protect goats against TB in laboratory and field conditions 18,20 , as well as cattle 21 , wild boar 22,23 , red deer 24 , badgers 25 and wild pigs 26 . HIMB represents an interesting alternative to live-attenuated BCG vaccine since the deployment logistics are simpler and the strain survival is not required 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is a certain degree of background regarding the inactivated vaccine candidate based on M. bovis (HIMB), that have been reported to protect goats against TB in laboratory and field conditions 18,20 , as well as cattle 21 , wild boar 22,23 , red deer 24 , badgers 25 and wild pigs 26 . HIMB represents an interesting alternative to live-attenuated BCG vaccine since the deployment logistics are simpler and the strain survival is not required 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed for evaluating whether this vaccination scheme could reduce the TB lesion prevalence in adult boars. The effectiveness of HIMB was also proved in Molokai wild pigs, where the oral vaccination induced a modest degree of infection containment [16].…”
Section: Wild Boarmentioning
confidence: 95%
“…Inactivated vaccines are expected to be more stable in baits (i.e., under high environmental temperatures) and safer as they are based on dead bacteria [14]. Recent studies have begun to address these concerns by demonstrating that oral vaccination with a HIMB successfully protects captive wild boar (Sus scrofa) [15], Molokai-origin wild pigs [16], red deer (Cervus elaphus) [17] and badgers (Meles meles) [18] against progressive disease. Field studies have also shown protective effect of oral HIMB vaccination in piglets against TB in endemic free-ranging wild boar populations [14].…”
Section: History and Evolution Of Tuberculosis Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…A live vaccine (BCG) for badgers is only licensed in the UK for intramuscular delivery, and its use in oral baits is promising, although the use of a live vaccine at a sufficient protective dose complicates the delivery in the field, especially at high environmental temperatures, impacting the survival of the vaccine [16]. The efficacy of a heat-inactivated M. bovis (HIMB) vaccine has also been assessed in different species, such as wild pigs [17], red deer [18], wild boar [19][20][21], goats [22,23], sheep [24] and zebrafish [25]. A recent experimental study in Spain showed a similar reduction in bacterial loads and lesion scores in BCG and HIMB orally vaccinated badgers [26] compared with non-vaccinated controls.…”
Section: Introductionmentioning
confidence: 99%